Combined recurrent laryngeal nerve monitoring and one-lung ventilation using the EZ-Blocker and an electromyographic endotracheal tube - Moritz, Andreas; Schmidt, Joachim; Schreiner, Waldemar; Birkholz, Torsten; Sirbu, Horia; Irouschek, Andrea (Journal of Cardiothoracic Surgery, 2019)
Background: Intraoperative neuromuscular monitoring (IONM) is a widespread procedure to identify and protect the recurrent laryngeal nerve (RLN) during thyroid surgery. However, for left thoracic surgery with high risk of RLN injury, both reliable recurrent laryngeal nerve monitoring and one-lung ventilation could interfere. Methods: In this prospective study, a new method for IONM during one-lung ventilation combining RLN monitoring with an electromyographic (EMG) endotracheal tube (ETT) and lung separation using the EZ-Blocker (EZB) is described and its clinical feasibility and effectiveness were assessed. Results: A total of 14 patients undergoing left upper lobe surgery and left upper mediastinal lymph node dissection were enrolled. The EZB was introduced and positioned without any problems and sufficient lung collapse was achieved in all patients. No tracheobronchial injuries or immediate complications occurred. A stable EMG signal was present in all patients and no RLN palsy and no negative side effects of the NIM EMG ETT or the EZB were observed postoperatively. Conclusions: The described method is technically feasible, easy to apply and save. It provides both reliable IONM and independent lung separation for optimal surgical exposure. The combined use of the EZB and the NIM EMG ETT might reduce the risk for RLN palsy and impaired lung separation during left thoracic surgery with high risk for RLN injury.
CRIS-Team Scopus Importer:2019-07-02
Keywords: EZ-Blocker; Intraoperative monitoring; One-lung ventilation; Recurrent laryngeal nerve; Thoracic surgery